Digital transformation of retail stores: The impact of digitalisation and omni-channel retail on the customer journey - Anna-Katharina Weiler; Klaus Mühlbäck; Ruth Schöllhammer (PraxisWISSEN Marketing, 2018)
The customer 4.0, who is especially influenced by the increasingly digital retail environment and mobile devices, is more and more empowered within the economy. Accordingly, high involvement customers are demanding companies to implement new strategies and to offer an integrated customer experience throughout offline and online channels. These demands imply both the digitalisation within the physical retail stores, for example through digital screens, as well as the implementation of the Omni-channel approach including the linkage of offline and online retail, for example through a click and collect concept. This digital transformation is aiming to offer the customer a neatless and consistent customer experience throughout all channels. The increasing necessity to create a neatless customer experience is leading to a customer journey throughout digital and analog. This study is therefore aiming to state the changed touchpoints and the new journey of the customer 4.0 as well as the implications for strategies and operative activities from a company perspective. In the course of this study, an essential part was the execution of a qualitative research in the form of expert interviews and through an online survey. The conducted research led to an in-depth insight of the relevance of digitalisation in-store and of the Omni-channel approach, and the following impact on the customer journey. – – Der Kunde 4.0, der stark durch eine zunehmend digitale Einzelhandelswelt und mobile Endgeräte beeinflusst ist, gewinnt zunehmend an Marktmacht. Entsprechend verlangen High-Involvement-Kunden von Unternehmen neue Strategien und Angebote, um ein ganzheitliches Einkaufserlebnis über Offline- und Onlinekanäle hinweg zu ermöglichen. Diese Erwartung führt sowohl zur Digitalisierung innerhalb des stationären Einzelhandels, z.B. durch Touchscreens, wie auch zur Etablierung eines Omni-Channel-Ansatzes einschließlich einer Verbindung von Offline- und Onlinehandel, z.B. durch sog. Click-and-Collect-Konzepte. Dieser Prozess der digitalen Transformation zielt darauf ab, dem Kunden ein durchgängiges und konsistentes Einkaufserlebnis über alle Kanäle hinweg zu ermöglichen. Die zunehmende Notwendigkeit, ein durchgängiges Einkaufserlebnis zu schaffen, führt zu einer Customer Journey sowohl durch digitale wie auch analoge Kanäle. Diese Studie befasst sich entsprechend mit den veränderten Touchpoints und der neuen Customer Journey 4.0 wie auch mit den Auswirkungen auf Strategien und operatives Vorgehen der Einzelhandelsunternehmen. Ein wesentlicher Teil der Studie war die Durchführung einer qualitativen empirischen Analyse mittels Experteninterviews sowie einer Online-Erhebung. Die Studie ermöglicht einen tieferen Einblick in die Bedeutung der Digitalisierung und des Omni-Channel-Ansatzes für den Einzelhandel sowie auf den sich daraus ergebenden Einfluss auf die Customer Journey.
Keywords: 650; Omni-Channel Marketing; Retail Marketing; Digitalisation; Customer Journey; Customer 4.0; High Involvement Customer; Digital Transformation; Click and Collect; Retail Technologies; Customer Experience